(3EYQGH KdGKjf ShQIs - (3GHf NGdhjg , GdMSjf Hf CMeO Hf NGdhjg Hf MeOGf, CHh YHO Gddg,J (B370 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje gPG cJGH PcQJ ajg EYQGH KdGjf ShQI ef GdeaUd , HTQM CUhd cd MQa hJdNjU aQhYg s
(3BNQgG (B:s
(3hai GdUeJ SJQ ddZHi hEfeG UMjaI dH GdeQA Cf jJcdeG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B155 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B175s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3JaSjQ (B51) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs